2020
DOI: 10.1007/s11239-020-02190-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pulmonary embolism in non-critically ill COVID-19 patients. Predicting factors for a challenging diagnosis

Abstract: Recent studies suggest that thrombotic complications are a common phenomenon in the novel SARS-CoV-2 infection. The main objective of our study is to assess cumulative incidence of pulmonary embolism (PE) in non critically ill COVID-19 patients and to identify its predicting factors associated to the diagnosis of pulmonary embolism. We retrospectevely reviewed 452 electronic medical records of patients admitted to Internal Medicine Department of a secondary hospital in Madrid during Covid 19 pandemic outbreak.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 18 publications
13
101
2
6
Order By: Relevance
“…After excluding duplicates and preliminary screening, 151 full-text articles were assessed for eligibility and 130 studies were excluded for not meeting the inclusion criteria, leaving 23 investigation fulfilling the inclusion criteria ( Fig. 1) [1,3,4,8,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding duplicates and preliminary screening, 151 full-text articles were assessed for eligibility and 130 studies were excluded for not meeting the inclusion criteria, leaving 23 investigation fulfilling the inclusion criteria ( Fig. 1) [1,3,4,8,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…Although the concomitant comorbidities were not systematically recorded by all investigations, active cancer and previous venous thromboembolic events were reported in a small percentage of cases. Fourteen studies considered ICU patients [1 , 3 , 4 , 8 , [16] , [17] , [18] , [19] , [20] , 22 , 25 , 26 , 28] while fifteen provided data of subjects hospitalized in general wards [1 , 8 , 17 , 20 , 21 , 23 , 24 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . Seven studies reported the data of both ICU and general wards patients [1 , 8 , 17 , 19 , 20 , 26 , 28] .…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that a very high D-dimer cut-off (approximately 10 fold the standard threshold) may be associated to con rmed APE. A recent study reported that a D-dimer threshold of 2660 μg/L detected all subject with APE among hospitalized COVID-19 patients [21], and in the formerly mentioned study by Mestre-Gomez et al, the best cut-off point was 5000 ug/dL [20]. These cut-off values are much higher than those used to exclude pulmonary embolus in non-ICU patients [22][23].…”
Section: Discussionmentioning
confidence: 89%
“…These gures are much higher than the rates of APE observed in non COVID-19 ICU patients with sepsis or shock receiving guidelinerecommended thromboprophylaxis [18,19]. In one of the very few studies which describing thromboembolic events in non ICU COVID-19 patients, Mestre-Gomez et al found that 29 out of 91 subjects (31.9%) who underwent CTPA presented APE, after admission to the internal medicine department [20]. Our results con rm the nding of a high incidence of APE in internal medicine department non-critical COVID-19 patients.…”
Section: Discussionmentioning
confidence: 93%
“…The diagnosis of COVID-19 in most studies required the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by real-time polymerase chain reaction (RT-PCR), but some were based on high clinical suspicion without the PCR results. In the clinical studies, 16 and 5 studies reported the incidences of outcomes only in the ICU (2,3,8,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) or non-ICU settings (27)(28)(29)(30)(31), respectively. Seven studies reported the incidence of outcomes in the ICU, and non-ICU settings.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%